Integrating Sustainable Tourism into EU Strategies for Economic Security through a Comparative Regulatory Analysis - Bulat, Veronica (Acta Universitatis Danubius. Œconomica, 2025)
Objectives: This paper examines how sustainable tourism is integrated into economic security strategies in four advanced EU economies—Germany, France, the Netherlands, and Sweden—highlighting its growing role in promoting resilience and regional development. Prior Work: While EU strategies such as the European Green Deal and Transition Pathway for Tourism emphasize sustainability, limited comparative research explores how national policies align with these goals in well-developed member states. Approach: A qualitative comparative analysis was conducted using case studies of national tourism strategies and recovery frameworks, focusing on policy integration, stakeholder collaboration, and alignment with EU directives. Results: All four countries embed sustainability into tourism policy, linking it to economic recovery, climate goals, and community development. Germany and Sweden emphasize local engagement and SME support; France and the Netherlands prioritize green investment and regional balance. Despite shared EU goals, implementation varies across contexts. Implications: The findings inform academic discourse on sustainable economic development and support policy harmonization across the EU by showcasing diverse models of tourism governance and innovation. Value: This study contributes original insights into how sustainable tourism functions as a tool for economic security in high-performing EU economies, offering replicable policy practices and governance models.